Molecular docking n-((5-phanyl-6,11-dihydro-5h-[1,2,4]triazolo[1',5':1,6]pyrido[3,4-b]indol-2-yl)-methyl)-r-amide and evaluation of their biological properties - Fedotov, S. O.; Gotsulya, A. S.; Федотов, Сергій Олегович; Гоцуля, Андрій Сергійович (My University, 2024)
The purpose of the work. Theoretical justification for the search for biologically active compounds in a series of innovative N-((5-phenyl-6,11-dihydro-5H- [1,2,4]triazolo[1',5':1,6]pyrido[3,4-b]indol-2-yl)-methyl)-R-amide.
Keywords: тези доповідей